مشاكلُ الترجمة التي يواجهها طلبة الماجستير في الجامعات العربية - شـمّـاـس نـافـذ (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This paper addressed the major problems and difficulties encountered by many of the MA students of translation at Petra University, Jordan; Damascus University, Syria; and the Arab Higher Institute of Translation, Algeria. It focused on their linguistic errors and cultural mismatch cases in translating from Arabic into English. The major aim was to reveal the aspects of deviation that have been more problematic: the linguistic errors or cultural mismatch cases? These deviations were classified into linguistic errors and cultural discrepancies. The linguistic errors embraced the syntactic and morphological aspects of language, on the one hand, and the semantic features of word choice and collocation, on the other. The cultural mismatch cases reflected two different sets of social values in the native speakers of Arabic and English in the first, religious, text; but were minimal in the present, political text. Some of the linguistic errors and the cultural mismatch cases, however, induced pragmatic failure in understanding the English target text, but at different degrees. Finally, although it was impossible to mention and tabulate all of the deviations spotted out in the respondents’ translations, these errors and/or mismatch cases were evaluated in terms of frequency and degree of causing pragmatic failure; solutions were suggested. غايةُ هذا البحث إلقاءُ الضوءِ على المشاكل الرئيسة التي يواجهُها طلابُ الماجستير في الترجمة في جامعاتً عربية ثلاث: جامعة البترا، عمّان، المملكة الأردنية الهاشمية؛ جامعة دمشق، الجمهورية العربية السورية؛ والمعهد العالي العربي للترجمة التابع للجامعة العربية في الجزائر. لذلك، ركّز البحثُ على الأخطاء اللغوية وحالات التنافر الثقافية عند الترجمة من العربية إلى الإنكليزية. وكان الهدفُ الرئيسُ من البحث الكشفَ عن الانحرافات المسببة لأكثر المشاكل في الترجمة: الأخطاء اللغوية أم حالاتُ التباين الثقافي؟ ولقد صنِّفت هذه الأخطاءُ على أنها انحرافاتٌ لغوية أو تباينات ثقافية. شملت الأخطاءُ اللغوية الجوانب النحويةَ والصرفية من ناحية والخصائص الدلالية في سوء اختار الكلمة أو التلازم اللفظي، من ناحية أخرى. لقد عكست حالاتُ التنافر الثقافي مجموعتين مختلفتين من القيم الاجتماعية المتنوعة لدى الناطقين بالعربية والانكليزية في النص الأول، الديني؛ ولكنها كانت ضئيلة في النصّ الحالي، السياسي. وفد أدّت بعضُ الأخطاء اللغوية وحالات التباين الثقافي إلى فشل عملي لفهم النصّ الهدف، ولكن بدرجات مختلفة. وأخيراً، وعلى الرغم من استحالة ذكر وجدولة جميع الانحرافات في ترجمات المستجيبين، فقد جرى تقويمُ الأخطاء اللغوية وحالات التباين الثقافي جميعاَ من حيثُ تكرارُها ومدى تسببها في الفشل العملي لفهم النصّ المترجم. واقترحتْ حلولاً لتلك المشاكل.